2022
DOI: 10.1037/aca0000359
|View full text |Cite
|
Sign up to set email alerts
|

Visual preference for abstract curvature and for interior spaces: Beyond undergraduate student samples.

Abstract: Smoothly curved objects elicit feelings of pleasantness and tend to be preferred over angular objects. Furthermore, individual differences (i.e., art expertise, openness to experience, holistic thinking), and the complexity of the stimuli are known to moderate the effect. We extended the study of individual differences to 2 theoretically relevant groups. Study 1 compared liking for curvature in individuals with autism and a matched neurotypical control group (for age, gender, and IQ). Because preference for cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 87 publications
(163 reference statements)
3
35
1
Order By: Relevance
“…Conversely, contour had no effect on judgements of beauty among nonexperts, but they were more likely to enter curvilinear spaces than rectilinear ones. However, a more recent study did not confirm preference for curved interior spaces with quasi-experts in industrial design ( Palumbo et al, 2020 ), hence highlighting that individual differences might also depend on the specific training received in the area of expertise. Cotter et al (2017) also reported that artistic expertise, a personality trait such as openness to experience, along with other cognitive traits (i.e., holistic thinking) predicted higher preference for curvature using irregular polygons, but not using arrays of circles and hexagons.…”
Section: Introductionmentioning
confidence: 90%
“…Conversely, contour had no effect on judgements of beauty among nonexperts, but they were more likely to enter curvilinear spaces than rectilinear ones. However, a more recent study did not confirm preference for curved interior spaces with quasi-experts in industrial design ( Palumbo et al, 2020 ), hence highlighting that individual differences might also depend on the specific training received in the area of expertise. Cotter et al (2017) also reported that artistic expertise, a personality trait such as openness to experience, along with other cognitive traits (i.e., holistic thinking) predicted higher preference for curvature using irregular polygons, but not using arrays of circles and hexagons.…”
Section: Introductionmentioning
confidence: 90%
“…The data for this study were collected by Palumbo et al (2020) in the context of a larger study involving additional non-architectural stimuli. Here we will only describe the method relevant to the present analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, Palumbo et al (2020) extended the study of preference for curvature in architecture to two theoretically-relevant groups, namely persons with autism spectrum disorder and design quasi-experts. Regarding the former, Belin et al (2017) had found that unlike participants with neurotypical development, persons with autism spectrum disorder reported positive feelings with jagged-edged stimuli.…”
Section: Individual Differencesmentioning
confidence: 99%
See 2 more Smart Citations